URGENSI PEMBAHARUAN PENGATURAN PERIHAL HAK INDIKASI GEOGRAFIS SERTA HAK MEREK DI INDONESIA - Ketut Adi Wirawan (VYAVAHARA DUTA, 2024)
Indonesia is a country rich in natural resources. In its use, several products are produced through a production process which supports improving the economy in Indonesia. In protecting several goods that have been produced in Indonesia, this is regulated in Law Number 20 of 2016 concerning Marks and Geographical Indications which is an amendment to Law Number 16 of 2001 concerning Marks. However, in its development, this regulation has not been able to provide protection for local products produced by the community. This research is normative legal research which examines aspects of internal problems in positive law using a normative juridical approach. The result of this research is that there are additional rules regarding geographical indications in the regulations regarding brands, making the substance of the geographical indication rules in each article less clear so that they are still unable to provide optimal protection for the geographical indication products produced. There needs to be a link between the procedures for product registration in the regulations on brands and geographical indications so that each geographical indication product that has been registered can directly obtain a special product brand that is different from other products so that it can provide protection to products produced by local communities. Therefore, it is necessary to update this regulation, so that problems do not arise such as duplication by third parties on original geographic indication products produced by local communities.